Activation of persulfate by a water falling film DBD process for the enhancement of enrofloxacin degradation. (August 2022) - Song, Shilin; Zhang, Huihui; Han, Song; Xiao, Sisi; Du, Yansheng; Hu, Kun; Wang, Huijuan; Wu, Chundu
Abstract: A synergetic system of water falling film dielectric barrier discharge (DBD) plasma and persulfate (PS) was established and applied to enhance the enrofloxacin (EFA) degradation in this study. The simultaneous existence of electrons, reactive species, heat and UV–visible light in the DBD plasma system were utilized together to activate the PS to form SO4 − · and other reactive oxygen species (ROS), and then worked in synergy with the DBD plasma to oxidize the EFA. The obtained results verified that there was a significant increase in the degradation percentages of EFA (20 mg L −1 ) in the DBD/PS system, and the trend was more obvious under the condition of larger discharge power input. When 0.8 mM PS was added into the DBD system with 0.8 kW discharge power, the degradation percentage of EFA could reach 99.35% after 60 min treatment, the corresponding synergetic factor (SF) was 7.94. Analysis of the O3 and the H2 O2 concentrations in the DBD plasma system before and after the PS addition explained the activation of the PS by the HO·. The quenching experiments on reactive species suggested that SO4 - ·, HO·, and 1 O2 were all important reactive species for EFA degradation. The intermediates formed by the EFA degradation were detected and the degradation pathways were speculated. Results of toxicity analysis illustrated that the toxicity of the initial EFA solution decreased after degradation in the synergetic system of DBD/PS. Graphical abstract: Image 1 Highlights: A synergetic system of water falling film DBD plasma and PS was established. PS could be activated by simultaneous existing physical and chemical effects in the DBD system. SO4 − ·, HO·, and 1 O2 were all important reactive species for the EFA degradation. Toxicity of the initial EFA solution decreased after treating by the DBD/PS.